OBESITY IN CHILDREN: CLINICAL, METABOLIC AND INFLAMMATORY ASPECTS (International journal of medical sciences, 2026)
Childhood obesity has become one of the most serious global public health challenges of the 21st century. The prevalence of overweight and obesity among children and adolescents has increased dramatically over the past decades, leading to early onset metabolic disorders, cardiovascular complications, and psychosocial consequences. Obesity in children is not only a result of excessive caloric intake but represents a complex multifactorial disease involving genetic predisposition, environmental influences, endocrine mechanisms, behavioral factors, and chronic low-grade inflammation.Recent evidence highlights the role of adipose tissue as an active endocrine organ producing adipokines and pro-inflammatory cytokines that contribute to insulin resistance, dyslipidemia, hypertension, and non-alcoholic fatty liver disease (NAFLD). Early identification of risk factors and implementation of preventive strategies are crucial to reducing long-term morbidity and mortality.This article analyzes the epidemiology, pathophysiology, clinical manifestations, complications, diagnostic approaches, and modern management strategies of pediatric obesity..